TWO VIEWING THEORY ON ATMOSPHERE CORRECTION IN OCEAN COLOR ALGORITHM - Sisir Kumar Dash; Tasuku Tanaka; Ryutaro Tateishi (International Journal of Remote Sensing and Earth Sciences (IJReSES), 2006)
A new algorithm for retrieving optical thickness and surface reflectance, data in the visible bands from satellites is developed. The proposed algorithm is to solve the simultaneous equation of two unknown variables, i.e. aerosol optical thickness and surface reflectance (r). In term of difference from the conventional and, one directional retrieval algorithm, we do not need the spectral characteristics of aerosol. We solve the equation by forward calculation using the 6S transfer code. The two observational equations change linearly within the domain where we solve the solution. We estimate the chlorophyll-a concentration from the evaluated r. This method is validated against Global Imager (GLI) data, which has two independent data for one pixel in both tilting and nadir viewing. Keywords, GLI, 6S, Radiative Transfer, Reflectance, Rayleigh, Mie.